Postoperative delirium in older patients with cancer: the role of psychological distress and social support. Issue 1 (22nd March 2022) - O'Hanlon, Shane; Baxter, Mark; Hosie, Annmarie
Abstract : Purpose of review: Delirium is a common and important adverse event in the perioperative period. Older people with cancer are at significant risk, and outcomes are poor. There is increasing awareness of the effect of psychological distress and social support on pathogenesis and outcomes of delirium in this setting. This review aimed to describe recent research in this evolving area. Recent findings: Across six recent studies of postoperative delirium in older people with cancer, delirium incidence ranged from 8 to 19.8%. Poor social support and high levels of distress are implicated in the development of postoperative delirium. Distress can be related to negative emotional reaction to diagnosis, preconception of cancer diagnosis and interactions with the healthcare system. Prevention of delirium is key, and multicomponent interventions show evidence of effectiveness. 'Emotional distress' has been included in a new core outcome set for studies of interventions to prevent and/or treat delirium. Summary: Postoperative delirium in older adults with cancer is common and is associated with increased morbidity and mortality. Psychological distress and social support play an important role, but there are many unmet research needs in this area.